Employment and health of working parents: a joint effort to uncover hidden treasures in birth cohorts. (13th November 2019) - Albin, M; Bültmann, U; Casas, M; Lawlor, D A; Lendzhova, V; Leombruni, R; Lissaker, C; Lucas, R; Maule, M; Peters, S; Polańska, K; Sarac, J; et al.
Abstract: : Birth and child cohorts include a wealth of valuable and under-utilized data on employment and health of parents during pregnancy, at birth and often at one or more follow-up assessments. OMEGA-NET is a EU COST Action aimed at creating a network to optimize the use of European occupational, industrial and population cohorts and to promote health research on occupation and employment. Within this network, Task Group 3.3 is exploring the possibility of exploiting birth cohort data to investigate the interplay between health, socio-economic conditions, working life and work participation of parents around and after the birth of their children, identify gaps in knowledge, and devise strategies to fill them. Using a web-based database, www.birthcohorts.net, we have identified cohorts with occupational and health information in up to 200, 000 parents. Out of 47 cohorts with information on mothers, maternal employment status and occupational exposures during pregnancy were recorded in 18 and 35 cohorts, respectively. For paternal exposures, the corresponding numbers were 6 and 15. To exploit these data, many challenges have to be overcome, primarily harmonization of exposures and outcomes. Cohorts cover different time periods and geographical regions, which can be at the same time a challenge and a blessing, providing hints on causal effects and mechanisms. Other strengths of pooling birth cohorts include the life-course nature of data and the possibility to investigate neglected occupationally-related exposures like work-family conflicts and their effects on health. We argue that parental data collected in birth cohorts are a valuable under-exploited source of information that would allow cross-national comparisons of the relationships between work, career trajectories and health of young parents. Key messages: Birth cohorts hide a treasure of occupational and health information of young working parents. OMEGA-NET has plans to dig them out to investigate their interplay.